Depth Transitions of the Frontal Branch of the Facial Nerve: Implications in SMAS rhytidectomy. (December 2020) - Pankratz, Joseph; Baer, Jacob; Mayer, Catherine; Rana, Viren; Stephens, Robert; Segars, Larry; Surek, Christopher C.
Abstract: Background: Anatomy of the frontal branch of the facial nerve relative to the zygomatic arch and the superficial musculoaponeurotic system (SMAS) has been well described. The variability centers on the location where the frontal branch traverses from a deeper to more superficial plane in the SMAS. The goal of this study is to examine the depth transition of the frontal branch of the facial nerve relative to the zygomatic arch with hopes of pinpointing a caution zone for dissection to avoid nerve injury. Methods: The frontal branch of the facial nerve was dissected in 36 hemifacial fresh cadaver specimens. Pitanguy's line, the zygomatic arch, and temporal crest were marked. Measurements were taken from the zygomatic arch to the location where the frontal branch pierced the temporoparietal fascia. Locations of the superficial temporal artery (STA), the frontal branch cross relative to the lateral orbital rim and frontalis muscle were also measured. Results: In 94.4% ( n  = 36) of the specimens, the frontal branch was found to transition to an intra-SMAS plane approximately 9.6 mm above the zygomatic arch. In all specimens, the frontal branch transitioned to an intra-SMAS plane approximately 12.2 mm posterior to Pitanguy's line. Conclusions: This study describes a surgical "caution zone" centered on a point 9.6 mm above the arch and 12.2 mm posterior to Pitanguy's line, and related to the anterior branch of the STA. We hope this anatomical detail will help to decrease the likelihood of intraoperative injury to the frontal branch of the facial nerve.